The jarlyk on appointment of amir-e tuman from the “Dastur al-katib” and status of temnik in the uluses of Hulagu, Jochi and Chagatay - Abzalov L.F.; Gatin M.S.; Mustakimov I.A.; Pochekaev R.Yu. (Золотоордынское обозрение)
Research objectives: This study aims to characterize the legal status of the emir of the tumen (i.e., miriarch) in the Chinggisid states, including the uluses of Hulagu, Jochi, Chagatay, and the Timurid State. The focus is on their roles as military commanders and administrative officers, drawing from medieval legal documents, narrative sources, and prior research findings. Materials and methods of research: The primary materials under examination are the jarlyks contained within Muhammad b. Hindushah Nakhchivani’s “Dastur al-katib fi ta‘yin al-maratib,” in its original Persian form and in the German translation by J. von Hammer-Purgstall. Additionally, various medieval sources detailing the history of the Chinggisid states of the 13th–14th centuries, both of Oriental and Russian origin, are considered. The research methods employed encompass historical-legal, diplomatic, and comparative historical analyses, forming an interdisciplinary approach that enables the comparison of diverse sources in the pursuit of authentic information. Scientific novelty: This work represents the inaugural Russian translation of the first jarlyk regarding the appointment of the emir of the tumen sourced from the ”Dastur al-katib.” It distinguishes itself by employing an interdisciplinary approach and cross-referencing with other source types. Results of the research: The analysis of the document facilitates the reconstruction of the legal status of the temnik, shedding light on their role as a military commander and high-ranking official within the uluses of Hulagu, Jochi, Chagatay (including the Timurid State). This includes an exploration of the qualifications expected of candidates for this position, as well as their associated rights and responsibilities. The diplomatic analysis contributes to a clearer understanding of the emir of the tumen’s position within the state hierarchy and underscores the significance attributed to candidates for this role by Chinggisid rulers.